2008
DOI: 10.1002/marc.200800229
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the Phase Diagram of an Aqueous Solution of Poly(N‐isopropyl acrylamide) by Controlled Microevaporation in a Nanoliter Microchamber

Abstract: This paper describes a poly(dimethylsiloxane) (PDMS)‐based microfluidic platform for constructing the phase diagram of poly(N‐isopropyl acrylamide) (PNIPAM) in aqueous solution. The PNIPAM solution was delivered into a nanoliter chamber through the main microchannel. An osmotic pressure difference was established between the chamber and the control microchannel by flowing a high‐concentration salt solution in the control microchannel. Controlled evaporation of water resulted in increasing concentration of PNIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
2
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 27 publications
3
47
2
5
Order By: Relevance
“…While reduced, this extra peak persisted even after prolonged incubation at 10 8 8C. Likewise,the scattering intensity profiles upon heating and cooling as obtained using am icrofluidic device of Zhou et al [24] with ascan rate of AE 0.5 Kmin À1 were essentially identical. Finally,O take et al [25] found agreement between DSC and visually determined T dem obtained at aheating rate of 1Kmin À1 however the values obtained upon cooling were typically 1K lower.…”
mentioning
confidence: 69%
“…While reduced, this extra peak persisted even after prolonged incubation at 10 8 8C. Likewise,the scattering intensity profiles upon heating and cooling as obtained using am icrofluidic device of Zhou et al [24] with ascan rate of AE 0.5 Kmin À1 were essentially identical. Finally,O take et al [25] found agreement between DSC and visually determined T dem obtained at aheating rate of 1Kmin À1 however the values obtained upon cooling were typically 1K lower.…”
mentioning
confidence: 69%
“…The microfluidic technology has been widely used in cell analysis and bioassay [6][7][8][9][10][11], because it is simple, portable, highly integrated [12], high in throughput and sensitivity [13], and it enables precise control of reaction conditions [14]. Bernard et al utilized flat surface of PDMS as the substrate for protein immunoassays [15].…”
Section: Introductionmentioning
confidence: 99%
“…Each of the points on the curve is a cloud point while the minimum of the curve corresponds to the LCST. The most common thermoresponsive polymers that exhibit LCST behaviour are poly(N-isopropylacrylamide) (PNIPAAm), [1][2][3][4] poly [2-(dimethylamino)ethyl methacrylate] (PDMAEMA), 5 poly(vinyl methyl ether) (PVME), 1 and poly(ethylene glycol) (PEG). 6,7 The chemical structures of their repeating units are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%